PENGENALAN DAN SOSIALISASI MICROSOFT PROJECT SEBAGAI SEBAGAI SARANA PENINGKATAN KOMPETENSI MANAJEMEN PROYEK DI RT 004 TEBET TIMUR DALAM - Aditya Herliawan; Mohamad Firdaus (CV. Denasya Smart Publisher, 2024)
This community service activity was conducted in RT 004, Tebet Timur Dalam, with the aim of introducing and promoting Microsoft Project as a tool to enhance project management skills. Microsoft Project is software that facilitates efficient project planning, management, and evaluation. The implementation methods included material delivery, discussions, and practical simulations using simple case studies relevant to the participants' needs. The results of this activity demonstrated that participants gained a basic understanding of project management concepts and fundamental skills in using Microsoft Project. This training is expected to enhance the community's ability to design and manage projects, whether for personal or communal purposes, thereby supporting more structured and effective activity management.